Subprodutos da agroindústria e indicadores externos de digestibilidade aparente em caprinos. - Salete Alves de Moraes (2007)
The nutrients intakes and digestibilities, energetic and nitrogen balance were evaluated and different methods of goat fecal product estimate in three assays, using agroindustry by-products and hay of tifton 85 (Cynodon sp.)as roughage. Twelve goat castrated males SRD, average alive weight of 18 kg had been distributed in a design entirely randomized with four levels of inclusion of by-products and six repetitions. The by-products had been residues of anatto seeds (Bixa orellana L.), dehydrated cashew bagasse (Anacardium occidentale) and cashew nut meal in levels of inclusion of 18, 36, 46 and 72% and 10, 15, 20 and 25%, respectively. The by-products had been gotten of industries processing of anatto seeds and fruit juice in the Northeast region, in the state of Ceará. Each experiment consisted of a period of 19 days, being fourteen days of adaptation and five days of collection of supplied food, refusal, excrements and piss. The estimate of the fecal production was carried through using excrement total collects and the external markers chromic oxide and Purificated Enriched Lignin (LIPE®), as external marker for comparison and validation, respectively. The dry matter intake (DMI), organic matter (OMI), crude protein (CPI) and gross energy (GEI) had increased linearly with the increment of the by-product of anatto in the diets, however, the EB apparent digestibilities, neutral detergent fiber (NDF) and acid detergent fiber (FDA) decreased linearly. The anatto by-product increment provided positive energy balance, without significant difference between the levels inclusions happening in the same way for the balance nitrogen, however, causing a significant difference (P<0,05) between the minor (18%) and the biggest level of inclusion (72%), in the nitrogen retention, with average values of 33,36 and 35,72%, respectively. The inclusion of the cashew by-product provided linear increase of all the nutrients evaluated. However, linear decrease was happened in apparent digestibilities of the NDF and ADF and quadratic decrease in the crude protein apparent digestibility with inclusion of the dehydrated cashew bagasse. The balance energetic was positive in all levels of cashew by-product inclusion (531.41 the 1256,31kcal for 18 and 72%, respectively), however, the nitrogen balance and nitrogen retention in 18%de inclusion was negative (-0,44 and -7,27 respectively). The meal cashew nut inclusion in diets increased the intake etereo extract significantly (0,98 percents units to each 1% of addition of meal cashew nut) and diminished the NDF and ADF intakes of diets. The CP and EE digestibilities were increased linearly with the inclusion of the meal cashew nut to each percents unit of inclusion, 1,15 and 0,22 units of increase in digestibilities had been found, respectively. The energy and nitrogen balance had been positive, but they had not significantly differed with the increment from the bran from the chestnut, reaching average values of 1629,83 kcal and 5,98 g, respectively. External marker LIPE® was valid to estimate fecal production and nutrients digestibility in goats at all the assays where it was used, if being similar to the method of total collection. The chromic oxide when used in the assays of the evaluation of anatto and the cashew bagasse dehydrated also it did not present significant difference with the method of total collection, although to reveal different in the assay of evaluation of the cashew nut meal, overestimating the apparent digestibilities of the assay.